Comparison of Impurity Profiles of Lipiblock (R) vs. Orlistat using HPLC and LC-MS/MS - Schneider, Alex; Wessjohann, Ludger A.; Severi, Juliana A. [UNESP]; Wagner, Vilegas [UNESP] (Colegio Farmaceuticos Provincia de Buenos Aires, 2012)
Comparative HPLC-UV and LC-MS/MS studies of impurity profiles of a reference sample (Xenical (R), F. Hoffmann La Roche Ltd., Switzerland) vs. generic (Lipiblock (R), EMS Sigma Pharma, a generic drug) were carried out with ethanol extracts of commercial samples. The generic formulation contained higher levels of common impurities as well as a considerable number of impurities not found in the reference product. The detected impurity profile of Lipiblock (R) revealed that it most likely is based on fermentation. Since the effect of the impurities is unknown, at this point fully synthetic Xenical (R) appears to offer a better safety margin than Lipiblock (R) which, however, compares quite well to other generic formulations.
Keywords: Generics; HPLC-MS/MS; HPLC-UV; Orlistat